The effect of cutting depth, feed rate, and cutting angle on surface roughness in the lathe process of aluminum 6061. - Suwanda, Totok; Ramdhan, Gilang Joy Habib; Ardiyansyah, Nur (Politeknik Negeri Lhokseumawe, 2024)
In the turning process, the machining parameters have a significant impact on the product quality. Consumers frequently request that certain industries adhere to product quality standards, especially regarding surface texture. Numerous product failures have resulted in dissatisfaction among the company's clientele because many lathe operators are fixated solely on product size drawings and are unaware of factors that can impact the surface roughness value. This investigation was conducted to ascertain how machining parameters affect surface irregularity. Variations in feed rates of 47.5 mm/min and 345.6 mm/min, cutting angles of 60° and 80°, and depths of cut of 1 mm and 3 mm were utilized to conduct the investigation on aluminum alloy 6061 specimens. The results of turning were evaluated for surface roughness using a surface roughness analyzer and a macro test to determine the structure of the surface roughness. Using the Minitab 2019 application, the obtained data was then analyzed to determine the influence of each trimming parameter working individually or simultaneously. Using the method of geometric factorial analysis, integrate the research parameters. The results indicated that the surface roughness increased as the feed rate increased; the lowest surface roughness was achieved with a depth of cut of 1 mm, a feeding rate of 47.5 mm/min, and a cut angle of 80°. In this study, the surface roughness value decreased as the cutting angle increased at lower levels of feeding rate, while the surface roughness value increased at higher levels of feeding rate.